2021
DOI: 10.1002/adom.202100723
|View full text |Cite
|
Sign up to set email alerts
|

Slow Energy Transfer in Self‐Doped β‐Conformation Film of Steric Polydiarylfluorenes toward Stable Dual Deep‐Blue Amplified Spontaneous Emission

Abstract: Exciton behavior is crucial for improving the optoelectronic property of a light‐emitting conjugated polymer. Herein, the photoexcitation dynamics of exciton migration and energy transfer in a self‐doped β‐conformation film of the polydiarylfluorenes (poly[4‐(octyloxy)‐9,9‐diphenylfluoren‐2,7‐diyl]‐co‐[5‐(octyloxy)‐9,9‐ diphenylfluoren‐2,7‐diyl], PODPF) are demonstrated. Compared to the first generation of the β‐conformation polyfluorene, poly(9,9‐dioctylfluorene) (PFO), energy transfer occurs in PODPF β‐confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…In this regard, the SVA method is a convenient and universal post-processing technology to simultaneously induce the formation of a submicrometer-scale structure on the surface and inside the film (SVA film). Finally, similar to the previous studies, , thermal annealing (TA) is a robust treatment method to cause interchain self-adjustment and obtain the crystalline structure of LCPs. According to the discussion given above, after TA at >220 °C (higher than its T g temperature), highly crystalline PODPF films (TA film) with a high fraction of β-conformational segments are obtained, which are negative for the deep-blue emission. , Therefore, moderate thermal treatment at 210 °C is selected here to induce the formation of trace β-conformation and weak interchain crystallization (Scheme c).…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…In this regard, the SVA method is a convenient and universal post-processing technology to simultaneously induce the formation of a submicrometer-scale structure on the surface and inside the film (SVA film). Finally, similar to the previous studies, , thermal annealing (TA) is a robust treatment method to cause interchain self-adjustment and obtain the crystalline structure of LCPs. According to the discussion given above, after TA at >220 °C (higher than its T g temperature), highly crystalline PODPF films (TA film) with a high fraction of β-conformational segments are obtained, which are negative for the deep-blue emission. , Therefore, moderate thermal treatment at 210 °C is selected here to induce the formation of trace β-conformation and weak interchain crystallization (Scheme c).…”
Section: Resultsmentioning
confidence: 72%
“…According to the discussion given above, after TA at >220 °C (higher than its T g temperature), highly crystalline PODPF films (TA film) with a high fraction of β-conformational segments are obtained, which are negative for the deepblue emission. 60,61 Therefore, moderate thermal treatment at 210 °C is selected here to induce the formation of trace βconformation and weak interchain crystallization (Scheme 1c). Finally, a series of submicrometer-scale morphological PODPF films are prepared via controlling the self-assembly behavior in solution and film states (Scheme 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyfluorenes (PFs) are a kind of blue light-emitting materials with excellent properties. 1,2 PFs with wide band gaps, excellent thermal and chemical stability, and high quantum efficiency are garnering an increasing amount of research interest. 3,4 In particular, studies on 9,9-disubstituted fluorene-based polymers have demonstrated that such PF derivatives can effectively enhance the solubility and processability of PFs.…”
Section: Introductionmentioning
confidence: 99%